Perceived behavioural intention of UiTM students towards visiting Kuching / Abdul Rahim Abdul Kadir - Abdul Kadir, Abdul Rahim (2014)
This study aims to understand the factors that encourage a person to perform an activity specifically what affects a traveller to take the decision of travelling to Kuching. The attitude-behaviour model is one of the models used by many previous researches to understand the relationship between attitude and its effect towards the behaviour of a person. Using the Theory of Planned Behaviour by Ajzen, this study clarifies the elements that affect UiTM Student’s behavioral intention. This theory will be used to evaluate the behavioral intentions of UiTM students towards visiting Kuching. There are three elements within the theory of planned behavior which is attitude, subjective norms and perceived behavioral control. The main objective to carry out this study is to investigate the attitude behavior relationship where attitude is the main predictor to behavioral intention. The specific objectives of the study are firstly to examine the relationship between attitude, subjective norms, and behavioral control towards behavioral intentions. Secondly, the specific objective is to find out the extent to which each variable influences UiTM Student’s behavioural intentions. The study was conducted by survey research specifically personally distributed questionnaires to the respondents which were UiTM students who visited Kuching. The result of the study finds that the element of Attitude which was the destination image contributed the most to the behavioural intention or willingness of the respondents to travel to Kuching. However, Subjective Norms and Perceived Behavioural Control also showed results that they both contribute to travellers’ behavioural intention with Subjective Norms being higher than Perceived Behavioural Control. This shows that a traveller’s attitude towards the destination contributes the highest to their willingness to travel with their Subjective Norms and Perceived Behavioural Control also affecting their decision.